Analisis Faktor Bekas Pengguna Dadah Terlibat Dalam Dakwah Kepada Penagih Aktif Perbincangan Menurut Hadis - Siti Nora’Aeshah, Zakaria; Mohamad Hilmi, Mat Said; Ahmad Haiqal Fitri, Ahmad Fuad (USIM PRESS, 2023)
Usually, duty as a preacher is pioneered by a group of individuals with Islamic studies backgrounds. This is because as a preacher, they have to guide the individual spiritually when needed. Therefore, it is a must for a group of preachers to have a wide knowledge of Islamic studies. However, there is also a group of preachers who have standard knowledge or only know the basics of religion but are active in preaching. This intended group is made up of former drug users who have contributed devotion, time, and energy to making drug addicts awake to the nature of God and faith. Because this contribution of devotion is a challenging task and not so popular, this research is intended to study the main factors contributing to their hard work in delivering preaching for this group of active drug addicts. After that, every factor that has been found will be debated according to the hadith perspective. Thematic methods are used in this research to analyse the data that has been obtained through data collection methodology and an interview with the preacher. The obtained data will be analysed using thematic methods and NVIVO software. The results show that there are 7 reasons that contribute to and motivate preaching: get busy to control addiction; advise others as well as yourself; reduce longing for drugs; get close to religion; help others in need; experience makes them understand active drug users; and also make up for old mistakes that surround people in drug addiction.